The Utility of Discriminant Analysis to Determine the Geographic Origin of Commercially Important Seafood and Aquaculture Species: A Meta-Analysis. Issue 4 (2nd October 2021) - Davis, Robert P.; Boyd, Claude E.; Davis, Donald Allen
Abstract: Elemental profiling is a process where element concentrations in tissues are used to discern group membership between a priori groups, such as geographic location. The goal of this meta-analysis was to determine the effectiveness of elemental profiling to discern the geographic origin of seafood products when coupled with discriminant analyses. Cohen's Kappa of discriminant analyses were calculated based on reported accuracies and calculated expected accuracies. A systemic literature review was conducted which generated 86 effect sizes from 43 studies. A random effects model was used to estimate Cohen's Kappa, and the average effect observed was 0.83 (±0.036 95% CI) with a p value of <0.001. Moderators were investigated as part of this analysis. There were no significant differences based on production method or geographic range, but differences were observed based on the type of tissue analyzed and taxa groups. Meta-regression was used to analyze the relationship between the effect size and the number of elements included in each analysis or sample size. There was no observed relationship between Kappa and the number of elements analyzed or the sample size of the study. Based on these results, recommendations for future studies that utilize elemental profiling are included.